Tax Avoidance Ditinjau Dari Capital Intensity, Leverage, Beban Iklan dan Kompensasi Eksekutif - Tika Marga Pratiwi; Anita Wijayanti; Rosa Nikmatul Fajri (Ekonomis: Journal of Economics and Business, 2020)
The use of high tax avoidance tactics by companies makes the target of government revenue not achieved. Thus making it the basis for testing capital intensity, leverage, advertising expense, executive compensation in influencing tax avoidance. Obtained a population of 14 food and beverage sub-sector companies listed on BEI in 2015-2018. With the use of purposive sampling technique as sampling, the final sample is 9 food and beverage sub-sector companies or 36 observational data. Multiple linear regression analysis was used as a testing method. The results obtained leverage and executive compensation affect tax avoidance,  conversely capital intensity and advertising expense do not affect tax avoidance.